All Bark, No Bite: Section 11 of India's Animal Welfare Legislation. (9th September 2020) - Banyal, Aakarsh; Shelke, Atmaram
Abstract: Speciesism is a bias that causes humans to accord themselves moral superiority in their dealings with non-humans. When speciesism permeates legislative thought, it leads to statutes that sacrifice the interests of non-humans to those of humans. The Prevention of Cruelty to Animals Act, 1960 ('PCA Act') is no exception. Section 11 of this Act enumerates specific instances that qualify as animal cruelty and prescribes punishment for the same. However, this section is riddled with statutory flaws, some owing their origin to speciesism: inadequate and sweeping punishments, the defective incorporation of the 'Doctrine of Necessity', and the limited recognition of cruel acts. This article seeks to analyse each of the aforementioned faults and prescribe solutions which would strengthen the animal welfare regime as a whole. While stressing on broadening the scope of punishable acts under section 11, along with the need for statutory language to reflect 'severity' of punishment, the article also argues for differentiated punishment drawn from a consequence-based model which acknowledges the trauma and suffering of the animal. The intention is to prompt a discourse on the ideal drafting of animal welfare legislation.